Analysis of the ways and methods of signaling pathways in regulating cell cycle of NIH3T3 at transcriptional level. Issue 1 (December 2015) - Chang, Cuifang; Niu, Zhipeng; Gu, Ningning; Zhao, Weiming; Wang, Gaiping; Jia, Yifeng; Li, Deming; Xu, Cunshuan
Abstract Background To analyze the ways and methods of signaling pathways in regulating cell cycle progression of NIH3T3 at transcriptional level, we modeled cell cycle of NIH3T3 and found that G1 phase of NIH3T3 cell cycle was at 5–15 h after synchronization, S phase at 15–21 h, G2 phase at 21–22 h, M phase at 22–25 h. Results Mouse Genome 430 2.0 microarray was used to detect the gene expression profiles of the model, and results showed remarkable changes in the expressions of 64 cell cycle genes and 960 genes associated with other physiological activity during the cell cycle of NIH3T3. For the next step, IPA software was used to analyze the physiological activities, cell cycle genes-associated signal transduction activities and their regulatory roles of these genes in cell cycle progression, and our results indicated that the reported genes were involved in 17 signaling pathways in the regulation of cell cycle progression. Newfound genes such asPKC, RAS, PP2A, NGR andPI3K etc. belong to the functional category of molecular mechanism of cancer, cyclins and cell cycle regulation HER-2 signaling in breast cancer signaling pathways. These newfound genes could promote DNA damage repairment and DNA replication progress, regulate the metabolism of protein, and maintain the cell cycle progression of NIH3T3 modulating the reported genesCCND1 andC -FOS . Conclusion All of the aforementioned signaling pathways interacted with the cell cycle network, indicating that NIH3T3 cell cycle was regulated by a number of signaling pathways.